2014
DOI: 10.15447/sfews.2014v12iss3art3
|View full text |Cite
|
Sign up to set email alerts
|

Climate Change Vulnerability of Freshwater Fishes in the San Francisco Bay Area

Abstract: Climate change is expected to progressively shift the freshwater environments of the San Francisco Bay Area (SFBA) to states that favor alien fishes over native species. Native species likely will have more limited distributions and some may be extirpated. Stream-dependent species may decline as portions of streams dry or become warmer due to lower flows and increased air temperatures. However, factors other than climate change may pose a more immediate threat to native fishes. Comparison of regional vs. state… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 11 publications
0
9
0
Order By: Relevance
“…Although many native fish species within the Delta are presumed to be highly vulnerable to extinction due to habitat alterations and climate change [70], we found evidence that a few native fishes such as the Sacramento Sucker and Tule Perch have increased in numbers within littoral habitats since the 1990s. Brown and Michniuk [24] found that Tule Perch catch in electrofishing surveys declined from 1980s to the early 2000s, but a more recent electrofishing survey in 2010–2011 found Tule Perch in even higher numbers than that found in the 1980s for a localized region around the western Delta [60].…”
Section: Discussionmentioning
confidence: 92%
“…Although many native fish species within the Delta are presumed to be highly vulnerable to extinction due to habitat alterations and climate change [70], we found evidence that a few native fishes such as the Sacramento Sucker and Tule Perch have increased in numbers within littoral habitats since the 1990s. Brown and Michniuk [24] found that Tule Perch catch in electrofishing surveys declined from 1980s to the early 2000s, but a more recent electrofishing survey in 2010–2011 found Tule Perch in even higher numbers than that found in the 1980s for a localized region around the western Delta [60].…”
Section: Discussionmentioning
confidence: 92%
“…Species-specific differences in temperature sensitivity and tolerances likely underlie the habitat range constraints in Delta Smelt and may explain increasing abundance and niche expansion in the non-native species. Climate change and increased occurrence of drought will likely continue to have a significant role in the shifted species assemblages in the SFE, favoring non-native fishes (as described in Quiñones and Moyle, 2014; Mahardja et al , 2017). For example, native species including Longfin Smelt ( Spirinchus thaleichthys ), Chinook salmon ( Oncorhynchus tshawytscha ), and Steelhead ( Oncorhynchus mykiss irideus) also exhibit lowered physiological tolerances and/or plasticity compared to non-natives (Cech and Myrick, 1999; Muñoz et al , 2015; Jeffries et al , 2016); however, there are some native species that will not be as vulnerable demonstrated by higher tolerances (to warming or salinity).…”
Section: Discussionmentioning
confidence: 99%
“…Despite well‐documented correlations between fish declines and changes in environmental variables such as temperature or food availability (Moyle et al ., ; Moyle & Leidy, ; Quiñones & Moyle, ), identifying the actual mechanisms driving fish population declines remains challenging. For anadromous species such as the A. medirostris , some evidence suggests that juvenile recruitment is a limiting factor in population recoveries (Hardy & Litvak, ; Hildebrand & McLeod, ).…”
Section: Introductionmentioning
confidence: 99%